Resilience Management at the Landscape Level: Fostering Mitigation and Adaptations to Global Change Based on Forest Socio-ecosystems - Lopez, Dardo Ruben; Cavallero, Laura; Carranza, Carlos; Easdale, Marcos Horacio; Peri, Pablo Luis (Springer, 2024)
Agroforestry landscapes provide a variety of ecosystem goods and services at both the farm and landscape levels. They also host thousands of rural people whose livelihoods depend on the forest. Forest sustainable management is needed for farmer’s development. This is complex because it implies the integration of biological and socio-productive diversity with spatiotemporal dynamic interventions. In this chapter, we propose to reduce the vulnerability of agroforestry systems to climate change through resilience management of social-ecological systems (SES) at the landscape scale. Specifically, we examine key properties of farm-level SES components, exemplify how they collectively interconnect at the landscape scale, and analyze the benefits of resolving social-ecological conflicts at the landscape scale. We include a case study documenting adaptation measures to climate change for rural families whose livelihoods depend on the forest. These innovations included improved rainwater harvesting and conservation, resource use efficiency and soil conservation, agroecological diversification, and socioeconomic organization. The promotion of the adaptation of rural families to global change allows families to remain inhabiting their lands. Rural emigration is associated with high values of unsatisfied basic needs. The innovations proposed in this chapter are indirectly associated with global change mitigation (fixing and/or maintaining a high amount of carbon in the soil and in agroforestry biomass). We conclude that we must consider the adaptation and mitigation capacity of socio-ecosystems at the farm and landscape scale to find solutions to the challenges of global change, namely, anthropogenic pressure and climate change. This reinforces the socio-ecological resilience of the entire forest landscape by maintaining ecosystem services (support and regulation services) and improving rural and urban population livelihoods.